2008
DOI: 10.1063/1.3029694
|View full text |Cite
|
Sign up to set email alerts
|

Electrical transport and thermoelectric properties of double filled compounds Ca0.1CexCo4Sb12 at low temperatures

Abstract: Electrical transport and thermoelectric properties of double filled compounds Ca0.1CexCo4Sb12 at low temperatures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…It is found that j L is the main source of j. Compared with the reference CoSb 3 , 11 In x Lu y Co 4 -Sb 12 compounds show very low j L . Meanwhile, we can see that the double-filled In 0.13 Lu 0.05 Co 4.02 Sb 12 has lower j L than that of the single In-filled In 0.09-Co 4 Sb 12 .…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…It is found that j L is the main source of j. Compared with the reference CoSb 3 , 11 In x Lu y Co 4 -Sb 12 compounds show very low j L . Meanwhile, we can see that the double-filled In 0.13 Lu 0.05 Co 4.02 Sb 12 has lower j L than that of the single In-filled In 0.09-Co 4 Sb 12 .…”
Section: Resultsmentioning
confidence: 85%
“…ZT of filled skutterudites is enhanced overall compared with that of the reference CoSb 3 . 11 The maximum ZT = 0.27 achieved at 365 K for In 0.13 Lu 0.05 Co 4.02 Sb 12 material is about one order of magnitude larger than that of CoSb 3 . The improvement of ZT is mainly attributed to the reduction of j L .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…8 shows the relation of ln σ versus T À 1/4 for CoSb 3(1 þ δ) with δ¼ 0.00, 0.01 and 0.02. Earlier researchers also reported that electrical resistivity follows variable-range hopping mechanism for CoSb 3 [25,[30][31][32]. Assuming the transport is dominated by the variable range hopping process, the thermopower can be expressed as follows [33]:…”
Section: Resultsmentioning
confidence: 96%
“…Many reports disclose that double filling is an effective method to enhance dual-frequency resonant phonon scattering [12]. Therefore, the double-filled skutterudites exhibit higher thermoelectric performance than the single-filled materials [13][14][15][16][17]. Indium (In) as an effective doping element in CoSb 3 -based skutterudites has attracted much attention.…”
Section: Introductionmentioning
confidence: 99%